Pengembangan Buku Ajar Berbasis Problem Based Learning di Sekolah Dasar - Fitria Devirita; Neviyarni Neviyarni; Daharnis Daharnis (Jurnal Basicedu, 2021)
The research objective was to develop thematic teaching materials based on Problem Based Learning in the two sub-theme of the diversity of living things in grade IV elementary schools. The development of teaching materials is motivated by the need for learning that can improve students' ability in problem solving, the ability to think critically, and foster curiosity. This type of research is development research (research and development). The development model used is the 4-D model which consists of the stages of defining, designing, developing and disseminating. The define stage will carry out an analysis of the curriculum, student analysis and needs analysis. The design stage is carried out by designing the lesson plans and teaching materials. The development stage is carried out by testing the validity, practicality and effectiveness test. The disseminate stage cannot be carried out because of the covid pandemic 19. The results of the research at the design stage obtained RPP and teaching materials designed by following PBL steps. The development stage based on the validity test of teaching materials is categorized as valid. At the effectiveness stage, the results showed that the teaching materials were effective so that they were easy to use by fourth grade students of SDN 03 Muaro. Based on these results, it can be concluded that the thematic learning tools based on Problem Based Learning on the sub-theme of the Diversity of Living Things for grade IV SD that have been produced can be declared valid, practical and effective.